A thermodynamic model for the pressure created by injecting liquid nitrogen into a boiler partially filled with water. (1st March 2023) - Chang, Chun-Ti; Lee, Yu-Cheng
Abstract: This study examines the interaction between a small amount of liquid nitrogen with nitrogen gas and water in a rigid boiler. A thermodynamic model is proposed, and simulations are conducted, focusing on predicting the fluids' equilibrium pressure. Two consecutive processes are assumed by the model: a mixing process of the injected liquid nitrogen and the nitrogen gas in the boiler, followed by a heat transfer process of the nitrogen and the water. The model is tested against the experimental data from Clarke et al. (Clarke, Martinez-Herasme, Crookes and Wen. International Journal of Multiphase Flow, 36(11):940-949, 2010), and the predicted pressures deviate from the data by less than 3%. Based on the model, this study further pursues the physical conditions favorable for maximizing the fluids' equilibrium pressure. The effects of the initial water temperature and the liquid nitrogen's quantity upon the pressure are examined. For the same initial water temperature, having more nitrogen raises the pressure. For the same amount of nitrogen, however, the pressure does not always increase with the initial water temperature, as the higher compressibility of warmer water ends up reducing it. These factors must be accounted for as one seeks to maximize the pressure. For this purpose, this study presents a simple framework to access the complicated thermodynamic responses of liquid nitrogen, nitrogen gas and water in direct contact. Highlights: A thermodynamic model is proposed for direct-contact interaction of LN and water. Two simple algorithms provide easy access to the complex fluid responses. Predictions agree with published experiments to within 3%. Boiler pressure increases with LN quantity but not the initial water temperature. Water compressibility underlies the non-monotonic variation of fluid pressure.